REAKSI PASAR ATAS PENGUMUMAN CORPORATE GORVERNANCE PERCEPTION INDEX (Studi Peristiwa di Bursa Efek Indonesia) - ARY WIRAJAYA, I GDE (Jurnal Ilmiah Akuntansi dan Bisnis, 2011)
Corporate governance perception index (CGPI) is a research project ongrading good corporate governance in Indonesia. This program is expected topositively influenced investors’ confidence to invest. This research examinesmarket reaction by detecting market reaction differences between high-rankand low-rank companies around the date of CGPI announcement in 2006 –2008 through seven days of observation.This research was conducted in Indonesia Stock Exchange. Sampleconsisted of 52 companies which were drawn using purposive samplingmethod. Data were analyzed using descriptive, statistic, and sensitivityanalysis. Result showed that market reacted to CGPI announcement, whichwas demonstrated by abnormal return and changes of stock traded volumearound the date of CGPI announcement. There was no significant differenceabout market reaction between high and low rank companies on CGPI during2006 – 2008. This implies that investors have not considered CGPI properly instock market transactions.
Keywords: corporate governa